Hydro-Meteorological Characteristics of the 1973 Catastrophic Flood in the Mahi Basin, India - Pawar, U.; Hire, P.; Sarukkalige, Ranjan; Rathnayake, U. (2023)
The September 1973 flood in the Mahi Basin was one of the most catastrophic and widespread in the 20th century. However, the hydro-meteorological characteristics of the 1973 flood were not studied. Therefore, an attempt has been made to analyze the meteorological and hydrological processes that led to the 1973 flood. Accordingly, daily rainfall data, river discharge, and cross-section data were obtained for the analysis. The 1973 flood was associated with very heavy rainfall resulting from two successive low-pressure systems (LPS) from 26 to 31 August 1973 and 2 to 5 September 1973. The rainfall variability in the Mahi Basin was 24% (annual) and 25% (monsoon) in 1973. The analysis showed that out of 69 rainfall stations, 13 stations received 100% rainfall in the monsoon season in 1973. Under the influence of the second LPS (7 and 9 September 1973), 21 rain gauge stations recorded very heavy rainfall (124.5–244.4 mm) on 8 September. As a result, the maximum discharge of the Mahi River (40,663 m3/s) was observed at Wanakbori on 9 September. The flood hydrograph denoted two flood peaks of 28,125 m3/s and 33,097 m3/s magnitudes resulting from LPS at Kadana. A newly constructed bridge (in 1972) on the Mahi River at the Kailashpuri village washed out due to a large discharge of 21,553 m3/s magnitude on 7 September 1973. The hydro-meteorological analysis of the 1973 flood specified the significance of the LPS in a flash flood disaster in the Mahi Basin. This study will benefit hydrologists and civil engineers creating design floods for the construction of the hydraulic structures in the Mahi Basin, and will help to avoid any future catastrophic floods.